Night owl - Mlynowski, Sarah; Myracle, Lauren, 1969-; Jenkins, Emily, 1967- (New York : Scholastic Press, 2021)
Tonight is the Big Night sleepover at Dunwiddle Magic School, when all the fifth graders stay overnight at school and participate in the scavenger hunt, except Nory's friend Elliott is attending a concert at rival Sage Academy where he plans to attend after the winter break--but if Nory can convince her fellow upside-down magic friends to take the hunt seriously, cooperate, and win, than maybe she can convince Elliott to stay at Dunwiddle.
3-6
4.0
Keywords: Magic -- Juvenile fiction; Treasure hunt (Game) -- Juvenile fiction; Sleepovers -- Juvenile fiction; Middle schools -- Juvenile fiction; Friendship -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Magic -- Fiction; Treasure hunt (Game) -- Fiction; Sleepovers -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Friendship -- Fiction; Cooperativeness -- Fiction; Fantasy; Fantasy fiction